Peningkatan Produktivitas Tanah Sulfat Masam dan Hasil Padi Menggunakan Bioarang dari Limbah Industri Penggergajian Kilang Kayu - Syamsul Bahri; Adnan Amin; Iwan Saputra (Institut Pertanian Bogor, 2024)
The study aims to analyze three aspects. (1) Formulation of biochar from wood refinery sawmill waste at pyrolysis temperatures of 450°C and 550°C with pyrolysis times of 2 and 4 hours. (2) The best wood refinery sawing waste biochar dosage to improve the chemical quality of acidic sulfate soil through improving soil pH, Al-dd, N, P, and K of the soil. (3) Growth and production of paddy on acidic sulfate soils by application of ameliorant biochar of waste sawmill wood mill. The research was conducted in acidic sulfate soil in a screen house in the Experimental Garden of the Faculty of Agriculture, Syiah Kuala University. Soil samples and biochar were analyzed at the Soil and Plant Research Laboratory of the Faculty of Agriculture. The study was an experiment using a factorial complete randomized design with two factors: the temperature and pyrolysis time and the dose of biochar. The results showed that the application of biochar waste from sawmill wood refineries had a very significant and significant effect on improving the quality of acidic sulfate soil and the growth and production of rice fields. The formulation of biochar at a pyrolysis temperature of 550°C for 2-hour pyrolysis with 20 tons/ha is the best improvement in acid sulfate soil quality, growth, and rice field production. Keywords: acid sulphate, biochar, paddy